Parenting Management in Bhayangkara Character Building - Endy Desianto; R. Kempa; J. E. Lekatompessy (International Journal of Education, Information Technology, and Others, 2022)
One of the goals of parenting is the formation of students' Bhayangkara character, a character which is a crystallization of the values ​​contained in Tribrata and Catur Prasetya. These basic values ​​undergo a crystallization process, namely a process of deposition and determination of the final stage of character values ​​until they are finally crystallized into 12 characters, a value that is considered the most appropriate of a number of character values ​​to be developed within the Indonesian National Police organization (Polri). This study aims were to explore the extent to which parenting management in the context of forming the Bhayangkara character in the SPN Polda Maluku is applied. This research were conducted at the SPN Polda Maluku from December 2021 to March 2022, the approach used in this study used a qualitative descriptive approach and the research object consisted of 10 informan. The results of this study indicate that the planning carried out by the SPN Polda Maluku is to prepare a written program, arrange a caregiver device and prepare students in the composition of platoon and company ties. In the implementation aspect, the caregivers describe, explain and apply the internalization program for the 12 character values ​​of Bhayangkara which is integrated with parenting patterns for students during the education period. The evaluation is carried out in several stages, the initial stage is by compiling a mental assessment of students, the second stage is carrying out evaluation meeting activities and at the final stage, documenting, recording and distributing the evaluation results to all caregivers. Internal supporting factors are caregiver performance, care facilities, care evaluation meetings and program planning. Internal inhibiting factors are the ownership of certified caregivers, damaged cabinets, budget support and the lack of health workers. Internal supporting factors are indirect caregiver support, parenting activities in synergy with the National Armed Forces (TNI) and support from the TNI and the Village Government. External inhibiting factors are the different education period for Noncommissioned Officer Candidate School (Secaba) TNI and the policy of shortening the education period from Lemdiklat Polri.